Electric-powered wheelchair with stair-climbing ability. (24th July 2017) - Tao, Weijun; Xu, Junyi; Liu, Tao
As an autonomic and convenient assistance device for people with disabilities and the elderly climbing up and down stairs, electric-powered wheelchairs with stair-climbing ability have attracted great attention in the past two decades and some various electric-powered wheelchairs with stair-climbing were developed. By using the developed electric-powered wheelchairs with stair-climbing, many patients with walking difficulties are able to descend the stairs conveniently to participate in outdoor activities, which are beneficial to both their physical rehabilitation and mental health. In this article, a review of electric-powered wheelchair with stair-climbing current technology is given and its future tendency is discussed to inform electric-powered wheelchair with stair-climbing researchers in the development of more applicable and popular products. Firstly, the development history is reviewed and electric-powered wheelchairs with stair-climbing are classified based on an analysis of their stair-climbing mechanisms. The respective advantages and disadvantages of different types of electric-powered wheelchairs with stair-climbing are outlined for an overall comparison of the control method, cost of mechanical manufacture, energy consumption, and adaption to different stairs. Insights into the future direction of stability during stair-climbing are discussed as it is an important aspect common to all electric-powered wheelchairs with stair-climbing. Finally, a summary of electric-powered wheelchairs with stair-climbing discussed in this article is provided. As a special review to the electric-powered wheelchairs with stair-climbing, it can provide a comprehensive understanding of the current technology about electric-powered wheelchairs with stair-climbing and serve as a reference for the development of new electric-powered wheelchairs with stair-climbing.